Polyval وPolyfitتقدير الملاءمة الجيدة لمجموعة نقاط معطيات باعتماد الإجراءين - محمد جاجان يونس الزبيدي; لمى اكرم عبدالله الصفار (PROSPECTIVE RESEARCHES, 2023)
The parameters confirmed that the appearance of the straight line is being as a path of many points which placed in a certain direction. However these points differ in its consistency from one place to another depending on the distortion which infects these points, which lead to the fact that the straight line does not appear in its accurate shape. In this paper, we have used the virtual linear relation of first order degree which give more identical data by using Matlab language version 7.2 to defined the best line points fit estimating using Polyfit and polyval procedures while reducing the error between the simple function and given line points by finding the estimating function which the summation of derivation line points for difference between the function and the input line points is minimum.